2019
DOI: 10.34101/actaagrar/1/2383
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant density on the yield of sweet potato

Abstract: A field study was conducted in South-East Hungary during the main cropping season of 2016, 2017 and 2018, with the objective of determining the effect of plant spacing on the productivity of sweet potato. Production technology experiments of four repetitions were set up in a randomized block design on sandy soil. The performed treatments consisted of four variations of plant spacing (row distance x plant-to-plant distance): 80 cm x 20 cm, 80 cm x 30 cm, 100 cm x 20 cm, 100 cm x 30 cm. The plant material was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…Una mayor densidad de plantas de 6.25 plantas m 2 (80 x 20 cm), según Szarvas et al (2018) a pesar de disminuir el rendimiento por planta, resulta en la producción de los mayores rendimientos de raíces reservantes por hectárea. Con una densidad de 62 500 plantas ha -1 (configuración de 80 x 20 cm) se puede lograr hasta 52.8 t ha -1 (Szarvas et al, 2019).…”
Section: Rendimiento Totalunclassified
See 1 more Smart Citation
“…Una mayor densidad de plantas de 6.25 plantas m 2 (80 x 20 cm), según Szarvas et al (2018) a pesar de disminuir el rendimiento por planta, resulta en la producción de los mayores rendimientos de raíces reservantes por hectárea. Con una densidad de 62 500 plantas ha -1 (configuración de 80 x 20 cm) se puede lograr hasta 52.8 t ha -1 (Szarvas et al, 2019).…”
Section: Rendimiento Totalunclassified
“…La densidad de siembra es una manera de controlar el tamaño de la raíz; mayores densidades de plantas por hectárea puede ser con el propósito de producir forraje y menor densidad repercutirá en el tamaño y calidad de raíces reservantes (Badge et al, 2021;Cusumano y Zamudio, 2013;Szarvas et al, 2018;Szarvas et al, 2019). En un marco de siembra de (0.90 m x 0.20 m), se siembra alrededor de 55 000 plantas ha -1 y se puede alcanzar rendimientos promedio de 25 t ha -1 hasta 58.5 t ha -1 (Szarvas et al, 2019).…”
Section: Introductionunclassified
“…Therefore, fresh root yield is the principal index for selecting elite varieties regardless of the usage of sweetpotato (Shumbusha et al 2019). Furthermore, the yield performance of sweetpotato is dominated by the quantity of storage roots per plant (Mekonnen et al 2021), which are affected by multiple factors of genes (Tang et al 2020), fertilization (Du et al 2020a, Si et al 2018) and planting density (Szarvas et al 2019). The spatial distribution of storage roots is an important trait for sweetpotato production.…”
Section: Importance Of the Selected Traits For Evaluating Marketable ...mentioning
confidence: 99%
“…This could be attributed to the compensation effect of closer spaced plants than the wider spaced plants by more number of tubers per plants and more average tuber weight which resulted in high tuber yield of potato per plant leading to higher tuber yield per plot. Masarirambi et al ., (2012); Lamessa and Zewdu [20]; Szarvas et al ., [21] and Takele et al,. [11] also studied the effect of spacing on yield of potato and concluded that at wider spacing yield was more than narrow spaced plants in potato and in sweet potato [22].…”
Section: Tuber Yield Per Plant (G) and Per Plot (Kg)mentioning
confidence: 99%